Procedural knowledge or conceptual knowledge? Developing the so-called proceptual knowledge in mathematics learning - Mardyanto Barumbun; Dian Kharisma (Beta: Jurnal Tadris Matematika, 2022)
[English]: Some students might have the proper knowledge to use mathematical procedures where relevant, but do they actually have a solid understanding of “why or how” those procedures work?  Such an incomplete understanding of mathematics concepts can be a stumbling block in students’ success in mathematics. This paper aims to propose and elaborate a framework for developing proceptual knowledge combining both procedural and conceptual knowledge on differentiation that are constructed on existing mathematics learning theories on how we understand mathematics, besides my personal reflections from the independent learning on differentiation. The theoretical and practical perspectives proposed in this article share insight with anyone in developing a more meaningful mathematics-independent learning experience, especially on topics with complex mathematical formulas or procedures, such as differentiation. [Bahasa]: Sebagian siswa mungkin memiliki pengetahuan yang tepat dalam menggunakan prosedur matematika secara relevan, namun apakah mereka sungguh memiliki pemahaman yang utuh tentang "mengapa atau bagaimana" prosedur matematika tersebut diperoleh? Pemahaman yang tidak utuh tersebut berpotensi menjadi penghalang kesuksesan siswa dalam memahami konsep matematika. Artikel ini mengusulkan kerangka kerja untuk mengembangkan proceptual knowledge (pengetahuan proseptual) pada materi turunan, yakni kombinasi pengembangan pengetahuan prosedural dan konseptual matematika yang dibangun di atas teori-teori pembelajaran matematika yang ada, serta hasil refleksi pribadi penulis dari proses belajar mandiri tentang konsep rumus diferensial. Perspektif teoritis dan praktis yang diusulkan dalam artikel ini dapat menjadi panduan bagi siapa saja untuk mengembangkan pengalaman belajar matematika yang lebih bermakna, khususnya pada topik dengan rumus dan prosedur matematis yang kompleks seperti pada turunan.